Exploring the Islamic perspective of pedagogical content knowledge among teacher educators in Tanzania - Ibnu Sheikh Gunda, Mnyero Janja; Alwi, Nor Hayati; Abd Rahman, Fadzilah; Krauss, Steven Eric (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Pedagogical content knowledge is a generative concept representing professional knowledge base for teaching. This proposed study focuses to explore the Islamic concept of pedagogical content knowledge among Muslim teacher educators in Tanzania. Data will be collected from 10 Diploma in secondary education teacher educators in Dar –es Salaam and Kilimanjaro regions through in-depth interview, observation and documentary review. Modified Interpretive Phenomenological Approach will be employed for thematic data analysis and interpretation. The results are expected to highlight meaning, nature and role of Muslim teacher educators’ Islamic perspective of pedagogical content knowledge.